Nutritive value of white oak (Quercus pubescens Wild.) browsed by goats - Parissi Z.M.; Nastis A.S. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
An in vivo trial was conducted in order to evaluate the nutritive value of white oak (Quercus pubescens Wild.) browse, during summer. Four indigenous goats (5-6 months, 24 ±0.9 kg BW) were placed in metabolic cages for a 20-d period. Fresh oak branches were offered to the goats and replaced, from 8 a.m. to 8 p.m., every two hours. The oak browse composition was: 124 g/ kg DM, 478 g/ kg DM and 118 g/ kg DM for CP, NDF and ADL, respectively. Average daily intake was 111 g DM/kg BW0.75. In vivo apparent digestibility of DM and CP of oak browse was 52% and 53%, respectively. Apparent digested nitrogen (N) was 12.2 g/day while apparent retention of N was 7.5 g/day. White oak can be considered as a valuable feed supplement for goats during summer, since it has a relatively high DM digestibility for this period and N retention was in excess of their maintenance requirements.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)